Decrease in the Gini Coefficient as a Result of the Distribution of BPNT during the Covid-19 Pandemic in the Province of Bangka Belitung Islands, Indonesia - Yusuf Munandar (Universitas Bangka Belitung, 2021)
The government issued a stimulus policy to reduce the impact of COVID-19, namely the Staple Foodprogram or extended BPNT program. One of the goals of implementing the BPNT program is to reduce the level ofincome inequality of the Indonesian people. Thus, this study aims to calculate and obtain the decrease in the GiniCoefficient as a result of the implementation of the BPNT program in the Province of Bangka Belitung Islands. Thisstudy uses the Counter Factual Analysis (CFA) method and the March 2020 Susenas data. This study concludes thatthe implementation of the BPNT program in 2020 is able to reduce the level of income inequality in the BangkaBelitung Islands Province, Indonesia, which is able to reduce the Gini Coefficient of the Bangka Belitung IslandsProvince by -0.43%. This study recommends that the provincial government of Bangka Belitung Islands as theimplementer of the Staple Food/BPNT program needs to improve the implementation of the BPNT program in theBangka Belitung Islands Province by ensuring Beneficiary Families/KPM (Keluarga Penerima Manfaat) can buyfood needs at the average price that applies in the market, ensuring KPM are able to choose good food ingredientsfrom quality, price and quantity, improving the quality of goods purchased by KPM and keeping the price moreaffordable, ensuring the availability of staple foodstuffs which are the main components of the program, ensuringthat realization in the field is according to a predetermined schedule, and ensuring the Covid-19 preventionprotocol can be running in the process of realization of the Staple Food/BPNT program.